2021
DOI: 10.3390/stresses1040017
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Tomato Landraces to Improve Seedling Performance under Salt Stress

Abstract: Salt stress is considered as one of the most frequent factors limiting plant growth and productivity of crops worldwide. The aim of the study was to evaluate physiological and biochemical responses of nine diverse tomato genotypes exposed to salt stress. In this regard, four-week-old seedlings of one modern variety, five landraces, the salt-sensitive accession of ‘Ailsa Craig’, the salt-tolerant wild accession of S. pimpinellifolium ‘LA1579’, as well as the vitamin C-rich S. pennellii introgression line ‘IL12-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…The tomato (Lycopersicon esculentum Mill.) the salt-sensitive cultivar, "Ailsa Craig" [99] was used in the present study. Seeds were collected from the Laboratory of Protected Horticulture, College of Horticulture, Nanjing Agricultural University, Nanjing, China and surfaced sterilized with 10% Sodium hypochlorite solution (NaClO), rinsed five times with deionized dd H 2 O (double distilled water) and incubated at 28 • C in Petri dishes under dark conditions until the emergence of the radicle.…”
Section: Plant Materials and Salt Stress Applicationmentioning
confidence: 99%
“…The tomato (Lycopersicon esculentum Mill.) the salt-sensitive cultivar, "Ailsa Craig" [99] was used in the present study. Seeds were collected from the Laboratory of Protected Horticulture, College of Horticulture, Nanjing Agricultural University, Nanjing, China and surfaced sterilized with 10% Sodium hypochlorite solution (NaClO), rinsed five times with deionized dd H 2 O (double distilled water) and incubated at 28 • C in Petri dishes under dark conditions until the emergence of the radicle.…”
Section: Plant Materials and Salt Stress Applicationmentioning
confidence: 99%
“…However, some cultivars still indicated higher growth under salt stress conditions (Fariduddin et al, 2012). The low salinity conditions stimulated plant growth and the accumulation of salts in the cell walls of some tomato cultivars (Kadoglidou et al, 2021).…”
Section: Resultsmentioning
confidence: 97%
“…The capacity of tolerance to salt stress ranges differently among the genotypes of tomatoes (Oliveira et al, 2022). It is possible to identify the most tolerant tomato genotypes to the effects of salinity based on the critical plant stage of cultivation (Kadoglidou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Kayess et al (2020) also observed a decrease in shoot fresh weight with a rise in salinity level. Kadoglidou et al (2021) observed a significant reduction in shoot fresh weight and shoot dry matter content under salt stress. Roots play an essential role in plant growth and development.…”
Section: Analysis Of Variancementioning
confidence: 89%